A Radiological Study of the Association of Facet Joint Tropism and Facet Angulation With Degenerative Spondylolisthesis - Ravi Ranjan Rai; Yash Shah; Siddharth Shah; Nigil Sadanandan Palliyil; Samir Dalvie (Neurospine, 2019)
Objective To study the association of facet joint angulation and joint tropism with degenerative spondylolisthesis (DS) through a comparison with a matched control group. Methods This radiographic study was carried out in 2 groups of 45 patients each. Group A contained patients with single-level DS, while group B (control) contained non-DS patients with similar age and degeneration who underwent surgery for disc prolapse or lumbar stenosis. DS was diagnosed based on translation of ≥ 3 mm on standing lateral radiography. Axial magnetic resonance imaging from L3 to S1 was utilized to assess the angulation of facet joints in relation to the coronal plane; a difference of ≥ 8° was considered to indicate tropism. Results Among 45 patients with DS, 15 were males and 30 females. Their mean age was 62.2 years. Facet tropism was identified in 20 of 45 patients at the level of DS, 12 patients at a level proximal to DS, and 15 patients at a level distal to DS. Facet tropism was found in 7 of the 45 patients in group B. At L3–4, facet tropism was observed in 13 patients (28.88%) in group A and 2 (4.44%) in group B. At L4–5, tropism was observed in 19 patients (42.22%) in group A and 5 (11.11%) in group B. At L5–S1, tropism was seen in 17 patients (37.77%) in group A and 2 (4.44%) in group B. Group A showed a significantly higher prevalence of multilevel facet tropism and tropism at levels adjacent to the DS level. A higher average angulation of facet joints was observed in the DS group, but the difference was not statistically significant at all levels. Conclusion The present study documented a statistically significant relationship between facet tropism and DS. A higher prevalence of facet tropism was also found in DS patients at non-DS levels, which is a novel observation. This finding supports the argument that facet tropism is a pre-existing morphological variation contributing to the development of DS, not a result of secondary remodelling.